Sigma-hole donor host systems for anion and ion-pair recognition - Bunchuay, T (2018)
This thesis describes the synthesis of acyclic, macrocyclic, and mechanically interlocked host molecules (MIMs) incorporating sigma-hole interactions including halogen and chalcogen bonding for anion and ion-pair recognition. Chapter 1 introduces the general aspects in the field of supramolecular host-guest chemistry with particular emphasis on themes relevant to the topic of this DPhil research project, specifically anion and ion-pair recognition followed by a review of the construction of mechanically interlocked architectures and their applications. Chapter 2 discusses rare examples of sigma-hole interactions mediated ion-pair recognition.The preparation of novel XB and unprecedented ChB heteroditopic host systems containing benzo[15]crown-5 are described, followed by investigation into ion-pair binding properties. The novel use of an ammonium[2]catenane integrated into the XB anion receptor capable of anion recognition in aqueous media is reported. Chapter 3 focuses on the exploitation of XB interactions for anion recognition and sensing in highly competitive aqueous media. An unprecedented relationship between anion template affinity and the yield of permethylated β-cyclodextrin-stoppered XB [2]rotaxane is demonstrated. Anion recognition properties of these rotaxane hosts in solvent media containing up to 50% water are subsequently investigated. Moreover, the novel cationic and neutral water soluble XB anion receptors based on 3,5-bis-(iodotriazole)pyridine, pyridine-N-oxide, and pyridinium motifs are synthesised to elucidate thermodynamic parameters of XB anion recognition in water using isothermal calorimetric analysis. Finally, the preparation of novel osmium(II)bipyridyl functionalised water soluble hosts are reported, and investigations in their anion recognition and sensing using electrochemical and fluorescence are detailed. Chapter 4 describes the effects of chelating XB receptors with a small bite angle on their anion recognition behaviour. A bidentate ortho-substituted iodotriazolium benzene motif is incorporated into acyclic, macrocyclic, and interlocked anion host molecules for their anion binding studies in solution phase, supported by solid-state structures of various anion complexed acyclic structural frameworks. Chapter 5 details the experimental procedures used in this work, including synthetic protocols and characterisation data for novel compounds.